Assessing the potential of soil carbonation and enhanced weathering through Life Cycle Assessment: A case study for Sao Paulo State, Brazil. (1st October 2019) - Lefebvre, David; Goglio, Pietro; Williams, Adrian; Manning, David A.C.; de Azevedo, Antonio Carlos; Bergmann, Magda; Meersmans, Jeroen; Smith, Pete
Abstract: Enhanced silicate rock weathering for long-term carbon dioxide sequestration has considerable potential, but depends on the availability of suitable rocks coupled with proximity to suitable locations for field application. In this paper, we investigate the established mining industry that extracts basaltic rocks for construction from the Paraná Basin, Sao Paulo State, Brazil. Through a Life Cycle Assessment, we determine the balance of carbon dioxide emissions involved in the use of this material, the relative contribution of soil carbonation and enhanced weathering, and the potential carbon dioxide removal of Sao Paulo agricultural land through enhanced weathering of basalt rock. Our results show that enhanced weathering and carbonation respectively emit around 75 and 135 kg carbon dioxide equivalent per tonne of carbon dioxide equivalent removed (considering a quarry to field distance of 65 km). We underline transportation as the principal process negatively affecting the practice and uncover a limiting road travel distance from the quarry to the field of 540 ± 65 km for carbonation and 990 ± 116 km for enhanced weathering, above which the emissions offset the potential capture. Regarding Sao Paulo State, the application of crushed basalt at 1 t/ha to all of the State's 12 million hectares of agricultural land could capture around 1.3 to 2.4 Mt carbon dioxide equivalent through carbonation and enhanced weathering, respectively. This study suggests a lower sequestration estimate than previous studies and emphasizes the need to consider all process stages through a Life Cycle Assessment methodology, to provide more reliable estimates of the sequestration potential of greenhouse gas removal technologies. Highlights: First assessment of the burdens associated with enhanced weathering and carbonation. Transportation of the material greatly impacts the sequestration potential. The quarry to field offsetting distance is 550 ± 65 km for carbonation. On Sao Paulo average, the practice emit 0.110 kg CO2 eq per kg of CO2 removed. The setup burdens of the practice reduce previous sequestration estimates.